PENGARUH SERVICE QUALITY GALERI INVESTASI DAN MOTIVASI INVESTASI TERHADAP KEPUTUSAN INVESTASI MAHASISWA FEB UNISMA DI PASAR MODAL - Faruq Wahyudi; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT This study aims to test Service Quality and Investment Motivation in influencing Investment Decisions on students of the Faculty of Economics and Business, Malang Islamic University. The population in this study were 505 people, and the sample in this study used purposive sampling technique totaling 83 people. Data analysis method used in the study is multiple linear regression, with F test for simultaneous and partial t test. The results of this study provide empirical evidence that partially Service Quality has a positive and significant effect on investment decisions (sig 0.004), Investment Motivation has a positive and significant effect on investment decisions (sig 0,000), and simultaneously states that Service Quality and Investment Motivation have a positive and significant to investment decisions (sig 0,000).Keywords: service quality, investment motivation and investment decisions